A thin line between invincibility and vulnerability : the interplay among engagement, exhaustion, and resilience - Stoffregen, Stacy Ann (Kansas State University, 2022)
This study focuses on first responders and their experience with work engagement, emotional exhaustion, and resilience over a three-month span. Drawing on Conservation of Resources theory and Job Demands-Resources model, the study examines the interplay between work engagement, emotional exhaustion, and resilience. Path analysis was conducted on the hypothesized model. Results show satisfactory fit and most of the hypotheses were fully or partially supported. Results showed (1) support for the stability of each respective study variable over three months; (2) emotional exhaustion consistently held a significant negative relationship with future levels of work engagement; (3) the relationship between work engagement and future reduced levels of emotional exhaustion was only partially supported; (4) the relationship between resilience safeguarding against future emotional exhaustion was also only partially supported. These findings highlight the need to prevent and manage emotional exhaustion as it can exacerbate other aspects of first responders’ psychological connection to their work. Theoretical and practical implications are discussed as well as limitations and future research directions.
Keywords: Work engagement; Resilience; Burnout; Emotional exhaustion; First responder